Endovascular treatment for basilar artery occlusion: whether the “weekend effect” affects time metrics and clinical outcomes at a comprehensive stroke center - Bao, Jianying; Shen, Guangchen; Shi, Haibin; Lin, Zheng; Liu, Sheng (Frontiers in Neurology, 2024)
Objectives This study aimed to evaluate whether the “weekend effect” would affect the time metrics and the prognosis of acute ischemic stroke (AIS) patients who underwent endovascular treatment (EVT) due to basilar artery occlusion (BAO). Methods Clinical data of AIS patients who underwent EVT due to BAO between December 2019 and July 2023 were retrospectively analyzed. At the time when the patients were admitted, the study population was divided into the weekdays daytime group and weekends nighttime group. In the subgroup analysis, the study cohort was divided into four groups: the weekdays daytime group, weekdays nighttime group, weekend daytime group, and weekend nighttime group. A good outcome was defined as a modified Rankin Scale score of ≤3 at 90 days after EVT. Time metrics [e.g. onset-to-door time (ODT) and door-to-puncture time (DPT)] and clinical outcomes were compared using appropriate statistical methods. Results A total of 111 patients (88 male patients, mean age, 67.7 ± 11.7 years) were included. Of these, 37 patients were treated during weekdays daytime, while 74 patients were treated during nights or weekends. There were no statistically significant differences in ODT (P = 0.136), DPT (P = 0.931), and also clinical outcomes (P = 0.826) between the two groups. Similarly, we found no significant differences in the time metrics and clinical outcomes among the four sub-groups (all P > 0.05). Conclusion This study did not reveal any influence of the “weekend effect” on the time metrics and clinical outcomes in AIS patients who underwent EVT due to BAO at a comprehensive stroke center.